Short‐term effects of biochar on soil heavy metal mobility are controlled by intra‐particle diffusion and soil pH increase. (28th October 2013) - Rees, F.; Simonnot, M. O.; Morel, J. L.
Summary Biochar, the solid product of biomass pyrolysis, can be used as a soil amendment to stabilize metals in contaminated soils. The effects of biochar on the mobility of metals in soils are, however, poorly understood. To identify the predominant processes, we focused on (i) a possible kinetic limitation by transport in biochar particles, (ii) the evolution of biochar mineral phases and (iii) the effect of biochar on soil pH. Batch experiments were conducted to measure the sorption kinetics of copper (Cu), cadmium (Cd) and nickel (Ni) and the sorption‐desorption isotherms for lead (Pb), Cu, Cd, zinc (Zn) and Ni in a wood‐derived biochar. Sorption data were then compared with extraction test results using biochar with one acidic and one basic soil contaminated by Zn, Cd and Pb. Kinetic results showed that biochar particle sizes controlled metal sorption rate despite a similar specific surface area, which indicated a limitation by intra‐particle diffusion. Isotherms showed a partially reversible sorption to biochar following the order Pb > Cu > Cd ≥ Zn > Ni, which we explained primarily by the (co)precipitation of metals or their adsorption on specific biochar mineral phases. Effective metal immobilization was observed with biochar in both contaminated soils but could not be predicted from the sorption isotherms. This immobilization appeared to be governed by the soil pH increase, which induced a greater retention of metals on soil particles. Short‐term effects of biochar on contaminated soils may therefore be controlled by diffusion in biochar particles and by soil alkalinization processes.